FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN LAPORAN PERTANGGUNGJAWABAN TERHADAP KUALITAS LKPD - Karolina Dahay (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
Systems, Information Technology, and Government Accounting Standards. The study used is qualitative and quantitative data.  The research used quantitative data analysis: instruments test classical assumption test, and multiple regression analysis. The results show that Human Resources competency and the application of Government Accounting Standards have a significant effect on the quality of local government reports. In contrast, Internal Control System and Information Technology do not have a considerable impact. Together all factors have a significant effect on the quality of LKPDLocal Government Reports.